2016
DOI: 10.1590/0104-0707201500003360014
|View full text |Cite
|
Sign up to set email alerts
|

Dificuldades De Cuidadores De Pacientes Em Cuidados Paliativos Na Estratégia Da Saúde Da Família

Abstract: This study's aim was to identify the main difficulties faced by caregivers of patients receiving comfort care at home and how they perceive the support provided by the Family Health Strategy. Qualitative research involving 50 caregivers providing comfort care to patients cared for by the Family Health Strategy in a city in the State of São Paulo, Brazil. The interviews were transcribed and analyzed using the Collective Subject Discourse methodological strategy. The results show that countless difficulties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 26 publications
0
12
0
22
Order By: Relevance
“…15,16 From this perspective, it was observed that possible weariness generated when facing these situations can be mitigated through the use of AD, since it is the expression of the patient's wishes and as such should be considered as a benefit in the process of providing to the patient health care. 11 This type of benefit was evidenced in categories 1 and 3, that is, for professionals, patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 From this perspective, it was observed that possible weariness generated when facing these situations can be mitigated through the use of AD, since it is the expression of the patient's wishes and as such should be considered as a benefit in the process of providing to the patient health care. 11 This type of benefit was evidenced in categories 1 and 3, that is, for professionals, patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…São escassos na literatura trabalhos que contemplem o perfil exato de cuidadora da usuária trabalhada nesse PTF, dada sua complexidade, já que é muito mais comum encontrar trabalhos a respeito de cuidadores de pacientes com doença crônica 8,9 , principalmente mental 10 e idosos 11,12,13 . Porém, ES, além dos demais membros do núcleo familiar, cuida também de uma idosa com doenças crônicas.…”
Section: Discussionunclassified
“…35 In the self-concept mode: symptoms of depression, 36 anxiety, 35 emotional stress, 36 somatization, 37 low self-esteem, 38 constant worry, feelings of uncertainty, 39 anger, guilt, 40 resentments, sadness, 35 feeling of frustration, [41][42] of burden, [43][44] feeling of lack of control over one's own life, 45 among others. In the role function mode: role conflict, 9 dissatisfaction with caregiver role.…”
Section: Family Caregivers From the Perspective Of Roy's Adaptation Mmentioning
confidence: 99%